A major leak in a crude oil tank: Predictable and unexpected root causes. (June 2019) - Cirimello, Pablo.G.; Otegui, Jose L.; Ramajo, Damián; Carfi, Guillermo
Abstract: A 2000 m 3 washer tank at a crude oil treatment plant suffered a structural collapse, involving total loss of integrity. A fast fracture initiated in a sector of the shell with a severe thickness reduction due to combined internal and external corrosion. The fracture bent and propagated horizontally, at the shell-roof intersection and at the joint between second and third courses, causing the almost instant opening of a large window. Due to the large initial leakage flow, the containment enclosure wall could not hold the spilled mixture of water and crude oil. The fast leaking wave damaged the breakwaters at the top of the wall, overpassed the enclosure and pushed out a sliding gate, thus causing total liquid leakage. Fracture and computational fluid dynamics models were developed to understand the origins of the failure, as well as to reconstruct the sequence of events. Deficiencies in tank construction, maintenance adequacy, and corrosion prevention were found to be the main root causes of the failure. Highlights: Crude oil spill surpassed containment enclosure, costly remediation. Tank collapse due to internal and external corrosion, fracture opened large window in shell. Root cause analysis and computational fluid dynamic modeling performed. Plates from dissimilar origins, undetected leaks and inefficient integrity management are main causes for failure.